Stakeholder’s resource mobilization and sustainability of government funded agricultural projects in Uganda: A case study of potato projects in Kabale District - moses Agaba (African Journal of Business Management, 2023)
This study sought to determine the impact of resource mobilization by stakeholders on the viability of government-funded agricultural initiatives, using a case study of the Kabale area. The lack of stakeholder participation in resource mobilization and decision-making has an influence on the long term viability of donor-funded potato projects in the Kabale district. This study required a prior study of the cross-sectional survey in order to lead to expected outcomes. 75 respondents provided information, and we integrated quantitative and qualitative analysis. The analysis, which was conducted at three separate levels, utilized descriptive, bivariate, and multivariate approaches. The descriptive analysis required the presentation of just one variable and its properties, frequency tables were used to illustrate the data. A Pearson correlation matrix was used to analyze the bivariate correlations between the dependent variable and the predictor components. At the multivariate level, the dependent variable was regressed against the updated predictor factors of sustainability of government projects. The results of a regression analysis showed that resource mobilization from stakeholders has a positive impact on the effectiveness of potato initiatives in Kabale District (coef = -0.890, p-value = 0.000). The main finding of this study is that resource mobilization by stakeholders has a substantial impact on the sustainability of potato projects. The study recommends putting greater attention on implementing stakeholder resource mobilization by defining the provision of capital, human resources, and availability of land in order to assure the sustainability of potato projects.